PROBLEMATIKA PENEGAKAN IZIN LINGKUNGAN DALAM PENCEGAHAN PENCEMARAN INDUSTRI DI INDONESIA - Ngainus Sofa; Fatikha Annisaushabra; Gisela Divani Fatikasari; Sela Amanatul Fatiha; Muhammad Adymas Hikal Fikri (CV. Denasya Smart Publisher, 2026)
Industrial development in Indonesia has had a positive impact on economic growth and national development, but on the other hand, it has also given rise to various forms of environmental pollution due to poor industrial waste management. Air, water, and soil pollution from industrial activities show that environmental protection still faces various challenges, particularly in environmental oversight and law enforcement. This study aims to analyze environmental permit regulations as an instrument for preventing pollution from industrial activities in Indonesia, analyze issues in environmental permit enforcement, and analyze efforts to optimize environmental permit enforcement in support of the Sustainable Development Goals (SDGs). This study uses normative legal research methods with legislative and conceptual approaches. The results show that environmental permits have a preventive function in preventing environmental pollution through the AMDAL (Environmental Impact Assessment) and UKL-UPL (Environmental Management and Monitoring) mechanisms. However, the effectiveness of environmental permit enforcement still faces various obstacles, such as weak oversight, low business compliance, inconsistent application of administrative sanctions, low public participation, and changes in licensing policies after the Job Creation Law that could potentially weaken environmental protection functions. Therefore, it is necessary to strengthen environmental oversight, implement strict sanctions, increase transparency in licensing, and optimize public participation to realize sustainable development and effective environmental protection.